Avaliação da repotenciação de uma termelétrica equipada com motores de combustão interna diesel por meio da recuperação de calor residual - Morawski, Alexandre Persuhn (2016)
The current scenario of the Brazilian electricity system has led to the dispatch of thermoelectric plants originally planned to give security to the system andshould not operate constantly.Theseplants were designedas low initial cost simple plants with low efficiency, not recovering effectively the waste heat. Plants with this profile,generating significant amounts of energy, consist in anopportunityto develop a study to better understand the situation of these plants in order to obtain the best energy efficiencies and higher net power output. In diesel engine thermoelectric plants, a significant amount of heat is wastedthrough cooling water andexhaust gas. Due this fact, a heat recovering system could be designed and attached to the thermoelectric plant, aiming increase the net electric power production with the same fuel consumption. Several WHR alternatives are possible, from Combine Cycle, that is the most usual, to more advanced technologies, asOrganic Rankine Cycle (ORC), Kalina Cycle and Absorption Cycle aiming intake air cooling. In thiswork the repowering alternatives for diesel internal combustion enginethermoelectric plantsare evaluated, through the recovery of waste heat. By analysis and thermodynamics balances, is defined which of these alternatives produces a bigger net power and efficiency increase, taking UTE Viana as a case study